Optimization of extraction of β-endoglucanase from the fermented bran of Aspergillus niger - Chandra, M. Subhosh (Springer India, 2010)
A local isolate of Aspergillus niger was cultivated under optimal growth conditions on wheat bran in solid state fermentation. β-endoglucanase from fermented bran was separately extracted with different solvents to test recovery of enzyme. Among solvents tested, distilled water served the best leachate. Conditions were further optimized with this leachate. Two washes of fermented bran with the leachate for 30 min each under shaking conditions in a ratio of 1 g of wheat bran: 4 ml of distilled water together yielded maximum recovery of 16.7 U/g of wheat bran.